Integrated supply chain model for sustainable poultry production in Bangladesh : a system dynamics approach - Shamsuddoha, Mohammad (Curtin University, 2014)
This study incorporates sustainability and supply chain theories to examine possible improvements, extensions and integration for the poultry production process. The study adopts positivist paradigm and ‘design science’ methodology with the support of ‘system dynamics’ method for a poultry case industry in Bangladesh. The simulation findings reveal that integration of poultry supply chains can achieve sustainable production of poultry products. This study also proposes several future directions and policy implications.